Innovation in Elementary School/Islamic Elementary School Curriculum Learning Models - Roso Murti; Moch. Farich Alfani (Penerbit Hellow Pustaka, 2025)
This research examines the need to improve the quality of education in elementary schools/Islamic elementary schools (SD/IS), which must be implemented through designing and creating creative and innovative learning models. The use of appropriate learning models can also create an effective learning environment. This is also a key point of change in a dynamic curriculum. In implementing the 2013 Curriculum in elementary schools/IS, several learning models can be applied, including the inquiry learning model, discovery learning model, project-based learning model, problem-based learning model, and cooperative learning model. Innovative elementary school/IS learning strategies in implementing the Merdeka Curriculum include: (1) the use of game-based learning (GBL); (2) multidimensional learning; (3) hybrid learning with parent involvement; (4) community-centered student learning; and (5) student-oriented learning. The implementation of the Independent Curriculum at the elementary and Islamic elementary school (SD/MI) level often utilizes project-based learning models. This is to support the achievement of the Pancasila-based student profile, which is a hallmark of the Independent Curriculum. In addition to the learning models from these two curricula, there are also learning models that teachers at the elementary and Islamic elementary school (SD/MI) can implement to prepare students for the Industrial Revolution 4.0 era, including mindful learning, experiential learning, transformational learning, immersive learning, the